Comprehensive biochemistry. Volume 34A, Molecular correlates of biological concepts - Laszlo, Pierre (Elsevier Science Publishers, 1986)
This volume focuses on the prehistory to modern biochemistry. Three topics, representative of the protracted emergence of biochemistry as a molecular science, are presented: respiratory pigments, enzymes, and nucleic acids. Particular emphasis is placed on the first two of these topics. The story of the elucidation of protein structure, with emphasis placed on the link between scientific and intellectual history, is told, virtually for the first time at this level of sophistication.
Keywords: biochemie; hemoglobiny; Enzymes; proteiny; Molecular Biology; Hemoglobins; enzymy; Biochemistry; Proteins; molekulární biologie